Customer Relationship Management (CRM) Based On Web To Improve The Performance Of The Company - yanto, Adi; asiah, Nur (Pandawan Sejahtera Indonesia, 2019)
Customer relationship management (CRM) is one of the model that can be used to maintain the relationship between customer and company. CRM is really helpful for the company to increase the customer interest toward the company, improve the economic condition, and improve the product promotion through the use of intimate customer knowledge. But, most of the company still can’t utilize CRM well, one of the problems is to increase the company performance. In this Journal will talk about the utility of CRM based on web to increase the company performance, the method that used in this journal is waterfall method which includes, analysis and systems engineering, requirements analysis, design, coding, programming, implementation and maintenance, and also literature review. With the e-CRM application is expected to provide benefits of the company, helps companies to know the wishes of customers, and can monitor the performance of employees, so the company is able to improve the performance of the company.